Levinas and Marion on Law and Freedom: Toward a new dialectical theology of justice1. (February 2016) - Wallenfang, Donald
There is a perennial ambiguity within the relationship between law and human freedom. Does law inherently promote freedom or restrict it? Emmanuel Levinas (1906–95) proposes that law – precisely Torah – is the gateway of freedom to the degree that law attests to the obligatory summons to responsibility for the other. In his 1964 Talmudic lecture entitled, 'The Temptation of Temptation', Levinas presents the paradoxical beginning of freedom in 'a non-freedom which, far from being slavery or childhood, is a beyond-freedom…overcoming the temptation of evil by avoiding the temptation of temptation'. However, Levinas's turn to Torah is not enough. His ethical phenomenology of proclamation must be paired with a contemplative phenomenology of manifestation so as not to engender action without considering what exactly gives itself to act upon. Enter Jean-Luc Marion (1946–). While Levinas's attention to the call of the other opens the ears to ethical exigency, Marion's attention to givenness opens the eyes to contemplative recognition of phenomena as they give themselves by themselves. An adequate assessment of the relationship between law and freedom requires a holistic phenomenology rooted in the polarity between ethics and givenness. The paradoxical relationship between law and freedom can be comprehended clearly only through a combined methodology which harnesses the fruitful tension between metaphysics and phenomenology. This article traces these dialectical relationships in method in order to account for the paradoxical relationship between law and freedom. Altogether, a move toward a new dialectical theology will be made that metes out justice to God, to humanity, and to the entire cosmos.